2000
DOI: 10.1345/aph.10134
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Possibly Associated with Fluvoxamine

Abstract: Despite the relatively safe and benign adverse effect profile of the selective serotonin-reuptake inhibitors such as fluvoxamine, clinicians should be cautious about seizures as an adverse effect, especially when the patient has even a remote history of seizure or head trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Small studies with a number of other SSRIs have also shown an indication for a possible beneficial effect in some neurological disorders: paroxetine and citalopram in patients with Parkinson's disease (Rampello et al 2002; Chung et al 2005), sertraline in patients with traumatic brain injury (Fann et al 2001), and citalopram and fluvoxamine in patients with epilepsy (Harmant et al 1990; Kim et al 2000; Favale et al 2003; Specchio et al 2004; Nakahira et al 2005). As distinct SSRIs have different affinities for the serotonin receptors, it is not possible to generalize the results of fluoxetine to all other SSRIs.…”
Section: Discussionmentioning
confidence: 99%
“…Small studies with a number of other SSRIs have also shown an indication for a possible beneficial effect in some neurological disorders: paroxetine and citalopram in patients with Parkinson's disease (Rampello et al 2002; Chung et al 2005), sertraline in patients with traumatic brain injury (Fann et al 2001), and citalopram and fluvoxamine in patients with epilepsy (Harmant et al 1990; Kim et al 2000; Favale et al 2003; Specchio et al 2004; Nakahira et al 2005). As distinct SSRIs have different affinities for the serotonin receptors, it is not possible to generalize the results of fluoxetine to all other SSRIs.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence from the literature that selective serotonin reuptake inhibitors cause seizure exacerbations. There are some isolated reports of seizures in adults treated with fluvoxamine (Kim, Craig, & Hawley, 2000; Trabert, Hohagen, Winkelmann, & Berger, 1995; Deahl & Trimble, 1991) and one case of status epilepticus (Loo, Piau, Galinowski, & Olie, 1987). There is a suggestion that fluoxetine might even have antiepileptic properties (Favale, Rubino, Mainardi, Lunardi, & Albano, 1995), although this has been challenged (Gigli et al., 1994).…”
Section: Part II Epilepsy and Behavioural Disordersmentioning
confidence: 99%
“…However, short‐term use for reducing the risk of COVID‐19 infection severity, may most likely be safe. 36 , 37 A scoping review on the exposure of patients to psychotropic drugs reached interesting and congruent results. Bonnet et al 38 reached a conclusion that exposure to SSRI or SNRI drugs may reduce mortality rate of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, short-term use for reducing the risk of COVID-19 infection severity, may most likely be safe. 36,37 A scoping review on the exposure of patients to psychotropic drugs reached interesting and congruent results.…”
Section: Discussionmentioning
confidence: 99%